Emerging Trends in Commerce and Management: A Multi-Disciplinary Approach (VOLUME-1) - Tomar, Ashu; Fatma, Aiman (AG Volumes, 2024)
"Emerging Trends in Commerce and Management: A Multi-Disciplinary Approach" is a timely and insightful exploration of the key trends shaping the future of business. The book delves into the ways in which new technologies, shifting consumer behavior, global market dynamics, and innovative management practices are influencing contemporary commerce and management.Covering a broad spectrum of topics, the book examines the impact of digital transformation, the growing role of sustainability and ethical business practices, the rise of e-commerce and digital marketing, and the integration of artificial intelligence and machine learning in decision-making processes. It also explores the changing landscape of corporate governance, financial management, human resource practices, and entrepreneurship.With contributions from experts across various domains, this book offers a multi-disciplinary perspective that emphasizes the interconnectedness of different fields in business management. It serves as both an academic reference and a practical guide for professionals who need to understand the emerging trends and adapt to the evolving business environment. The book encourages critical thinking and provides readers with the tools they need to anticipate and navigate the challenges and opportunities that lie ahead in the commerce and management sectors.